Features of food industry on the Internet: A case of Lithuania - Vida Davidavičienė; Jolanta Sabaitytė; Sigitas Davidavičius (International Entrepreneurship Review, 2017)
The objective of this paper is to identify and present the current situation of Lithuanian food industry sector in terms of online presence, use of e-marketing tools and internet strategy implementation, paying attention to food manufacturers, marketers, and food delivery (including fast food and restaurants). The following methods as comparative analysis of the scientific literature, secondary data analysis, data comparison and logical grouping, graphical representation of data, and descriptive statistics employed. For empirical study, it was decided to investigate online activities of the food industry sector of Lithuania using structured observation technique. Following assumptions were formed after study: companies of food industry are more oriented to Russia than to European market, and Baltic market is really important for this sector. It is necessary to investigate food industry sector activities and strategies in other regions, and to develop model of Internet strategy forming for food industry by online presence decisions. The originality of this work lies in studying some aspects of strategic and tactical decisions related to online presence of food industry companies of Lithuania.